Difficulties the performance of the leaders of the public secondary schools in Hail city from their point of view of guidance and professional guidance for their students - Alrowaished, Abdullah Hamoud; Alotibi, Fahad Abas (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the challenges to the performance of the administrators of public secondary schools for boys in Hail from their perspectives. The researcher used the descriptive-survey method and used a questionnaire, which was distributed to a sample of (344) school leaders. The results concluded that challenges to the performance of school leaders in promoting career guidance and counseling for students from their perspectives came with a (medium) degree and an average (3.11). For domains, the financial challenges came at the first level with an average (3.18) and administrative challenges came with an average (3.13); both of them came with a (medium) degree. Technical obstacles came with a (medium) degree and an average (3). According to the findings, the researcher suggested developing programs to reduce the administrative demands on school administrators, hiring a specialized and full-time career counselor for the vocational guidance process in secondary school, and proposing further research on the topic. The researcher also suggested providing adequate financial support for the school budget to help improve career guidance programs.